2021
DOI: 10.3390/plants10040751
|View full text |Cite
|
Sign up to set email alerts
|

Nanoimpact in Plants: Lessons from the Transcriptome

Abstract: Transcriptomics studies are available to evaluate the potential toxicity of nanomaterials in plants, and many highlight their effect on stress-responsive genes. However, a comparative analysis of overall expression changes suggests a low impact on the transcriptome. Environmental challenges like pathogens, saline, or drought stress induce stronger transcriptional responses than nanoparticles. Clearly, plants did not have the chance to evolve specific gene regulation in response to novel nanomaterials; but they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…The general impact of NM in plants has been reviewed recently [16][17][18][19][20], as well as the use of nanocarriers to deliver active compounds to plants [21][22][23], the broad applications of NM to improve plant growth and plant stress tolerance [24][25][26][27][28][29][30][31], and the potential of NM for plant disease management [32]. Here, we focus on TiO 2 (nTiO 2 ) and ZnO (nZnO) nano-formulations as plant protective and ameliorative agents against (a)biotic stress based on the reports released in the last five years of research, highlighting their potential to cope with drought and salinity stresses, as well as their potential in metal stress mitigation and plant protection.…”
Section: Introductionmentioning
confidence: 99%
“…The general impact of NM in plants has been reviewed recently [16][17][18][19][20], as well as the use of nanocarriers to deliver active compounds to plants [21][22][23], the broad applications of NM to improve plant growth and plant stress tolerance [24][25][26][27][28][29][30][31], and the potential of NM for plant disease management [32]. Here, we focus on TiO 2 (nTiO 2 ) and ZnO (nZnO) nano-formulations as plant protective and ameliorative agents against (a)biotic stress based on the reports released in the last five years of research, highlighting their potential to cope with drought and salinity stresses, as well as their potential in metal stress mitigation and plant protection.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies demonstrated that nanoparticles could also influence the gene expression of plants. [ 51,52 ] Thus, PS‐NPs possibly influence the gene expressions of FA synthesis‐related genes in grains. For FA synthesis and metabolism, acetyl‐CoA carboxylase OsACC1, [ 53 ] FA elongase ONI1, [ 54 ] long‐chain FA ω ‐alcohol dehydrogenase ONI3, [ 55 ] ω ‐6 FA desaturase OsFAD2‐1, [ 56 ] ω ‐3 fatty acid desaturase OsFAD7, [ 57 ] and OsFAD8 [ 58 ] play their respective roles in rice.…”
Section: Resultsmentioning
confidence: 99%
“…Así como analizar los posibles efectos genotóxico y citotóxico en plantas, debido a que las NPsAg de menor tamaño se internalizan en las células con efectos sobre la división y reparación celular (Panda et al, 2016;Bello-Bello et al, 2018;Castro-González et al, 2019). Esto contribuye a determinar sus futuras aplicaciones para la elaboración de nanopesticidas, nanofertilizantes, nanorreguladores del crecimiento, y nanomateriales para mejorar la producción en la agricultura actual (Shang et al, 2019;García-Sánchez et al, 2021). La utilización de las NPsAg…”
Section: Discussionunclassified